ASLIB Cranfield project - report on the first stage of a test on the Library catalogue of The English Electric Co. Ltd., Whetstone - Warburton, B.; Cleverdon, Cyril W.; Aitchison, Jean (Cranfield Institute of Technology, 1961)
At the request of the Director of the Aslib Cranfield Project, the Library of Engiish Electric Company at Whetstone agreed to allow the Project Staff to carry out a test on their catalogue. This was required in connection with the work of the project, more particularly in relation to the view that it was possible to carry out tests of this nature on existing indexes. From the project viewpoint, it was an experiment; as far as English Electric Company were concerned, it was hoped that the test might produce some information of value concerning their Facet catalogue.